A comparative study of pre- or subpectoral expander position with the fenestrated Acellular dermal matrix anterior coverage, on drainage volume and Seroma Formation after Non-Nipple-Sparing Mastectomy. Issue 9 (September 2021) - Suh, Young Chul; Kim, Jin Kwan; Kim, Na Rim; Choi, Jung Sik; Kim, Young Jin; Lee, Jung Ho; Jun, Young Joon
Summary: Background: It has been reported that the use of the acellular dermal matrix (ADM) in expander-based breast reconstruction is related to an increase in seroma-related complications. The aim of this study is to compare the actual drainage volume, time to drain removal, and seroma formation rate in patients with prepectoral expander placement with anterior coverage of a fenestrated ADM to those patients with partial subpectoral expander placement with inferior coverage of a fenestrated ADM. Methods: This is a single-surgeon retrospective review of patients who underwent prepectoral expander-based breast reconstruction following non-nipple-sparing mastectomy. Patient demographics, operative data, and complications were analyzed and multivariate linear regression analyses were conducted to evaluate the significance of factors that influences total volume of fluid formation. Results: A total of 89 breasts from 87 patients were included in the study. Twenty-seven breasts had prepectoral expander reconstruction and 62 breasts had partial subpectoral expander reconstruction. Mean total volumes of fluid formation (total drainage volume + additional aspirated volume) were not significantly different ( p  = 0.190) in the two groups. In the subpectoral group only, high body mass index (BMI) was correlated with the total volume of fluid formation among the independent factors. ( p  = 0.017) Conclusions: Although total drainage volume was not significantly different between prepectoral and subpectoral groups, prepectoral positioning of the expander can be a protective factor against seroma formation in high BMI patients. Further definitive studies with larger patient numbers are warranted to corroborate these data and draw definitive conclusions.